2002
DOI: 10.1051/animres:2002039
|View full text |Cite
|
Sign up to set email alerts
|

In situ evaluation of the protein value of soybean meal and processed full fat soybeans for ruminants

Abstract: -The rumen degradation and the intestinal digestion of dry matter (DM) and crude protein (CP) of different samples of soybean meal (SBM) and full-fat soybean (FFS) were determined using in situ techniques. Rumen effective degradability (ED) was determined in three rumen fistulated wethers on nine SBM samples, obtained by solvent extraction (SBM1 to 8) and by expelling (SBM9), and on five FFS samples, treated by extrusion (FFS1 to 4) and by toasting (FFS5). Intestinal digestibility (ID) in the original feed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
9
12
2
1
Order By: Relevance
“…These values are similar to those reported by Demir and Şekeroğlu (2000) (91.24%), by Nowak et al (2005) (90.5%, 91.3% and 90.8%), and by Griffiths (2004) (92.5%) and they were lower than those reported by Bargalea et al (1999) (96.25%, 96.27% and 96.28%). The CA values of ESB in present study ranged from 4.6% to 7.6% which are similar to the values reported by Bargalea et al (1999) (4.65%, 4.72% and 4.67%), by Demir and Şekeroğlu (2000) (4.81%), by Gonzalez et al (2002) (between 4.82% and 6.24%), by Griffiths (2004) (5.2%), by Nowak et al (2005) (5.1%, 5.2% and 5.2%). In the study NDF and ADF values of ESB were 9.3% to 13.5% and 6.7% to 10.7% respectively and they are lower than those reported by TroegelerMeynadıer et al (2006) (NDF: 27.8% and ADF: 14.8%) and by Nowak et al (2005) (NDF: 29.6%, 27.6%, 27.8%; ADF: 20.4%,19.3% and 19.2%).…”
Section: The Rumen Degradation Characteristics Of Extruded Full Fat Ssupporting
confidence: 91%
See 2 more Smart Citations
“…These values are similar to those reported by Demir and Şekeroğlu (2000) (91.24%), by Nowak et al (2005) (90.5%, 91.3% and 90.8%), and by Griffiths (2004) (92.5%) and they were lower than those reported by Bargalea et al (1999) (96.25%, 96.27% and 96.28%). The CA values of ESB in present study ranged from 4.6% to 7.6% which are similar to the values reported by Bargalea et al (1999) (4.65%, 4.72% and 4.67%), by Demir and Şekeroğlu (2000) (4.81%), by Gonzalez et al (2002) (between 4.82% and 6.24%), by Griffiths (2004) (5.2%), by Nowak et al (2005) (5.1%, 5.2% and 5.2%). In the study NDF and ADF values of ESB were 9.3% to 13.5% and 6.7% to 10.7% respectively and they are lower than those reported by TroegelerMeynadıer et al (2006) (NDF: 27.8% and ADF: 14.8%) and by Nowak et al (2005) (NDF: 29.6%, 27.6%, 27.8%; ADF: 20.4%,19.3% and 19.2%).…”
Section: The Rumen Degradation Characteristics Of Extruded Full Fat Ssupporting
confidence: 91%
“…In the study NDF and ADF values of ESB were 9.3% to 13.5% and 6.7% to 10.7% respectively and they are lower than those reported by TroegelerMeynadıer et al (2006) (NDF: 27.8% and ADF: 14.8%) and by Nowak et al (2005) (NDF: 29.6%, 27.6%, 27.8%; ADF: 20.4%,19.3% and 19.2%). NDF values of ESB were determined by Gonzalez et al, 2002 as between 12.3% and 19.6% which are also somewhat higher than the relevant values of this study but ADF values reported by same researchers (between 7.05% and 10.9%) were similar to ADF values in this study. CF values (5.6% to 9.5%) in the present study are similar to those reported by Demir and Şekeroğlu (2000) (5.48%), by Nowak et al (2005) (6.8%, 6.4% and 6.0%), but they are lower than those written by Griffiths (2004) (11%), by Bargalea et al (1999) (13.9%, 13.8% and 16.6%).…”
Section: The Rumen Degradation Characteristics Of Extruded Full Fat Ssupporting
confidence: 73%
See 1 more Smart Citation
“…This could be associated with the concentration of CTs; the greatest CT concentration in R. glutinosa leaves had the least DM disappearance of the potentially degradable fraction. The CTs depress DM degradability (Gonzalez et al, 2002;Gupta et al, 2011). In general, E. capensis leaves had the greatest values for slowly degradable fraction, effective degradability and rate of degradation c as compared to values recorded for other plants (P < 0.001).…”
Section: In Sacco Dry Matter Degradability Characteristicsmentioning
confidence: 80%
“…As a result, efforts have been made to protect good quality proteins from microbial actions. In SBM, obtained by solvent extraction, an important fraction of the CP (60-70%) is usually degraded in the rumen [12,16,22] and therefore, protection is of interest. Denaturation of proteins through treatment with acid solutions have been essayed with this purpose on different feeds [5,25,26], generally showing positive effects.…”
Section: Introductionmentioning
confidence: 99%